Marketing Based Decision Making Process in Engineering Design - Palani Raj, K.; Veeramani, G. (International Journal of Engineering and Technology, 2018)
Marketing based decision making process in engineering design is an important study required for industries. How to take efficient decision in design that influence marketing? Most of the engineering design decisions are based on consumer behaviour. Decision making in risk and uncertainty in engineering design is an important phenomenon. Cost and time are the two important factors that results loss because of inefficient decision and it affects marketing. Problems involved in marketing based engineering design and decision making process in solving problems is elaborately studied in this journal. How to choose a design in various alternatives, design process, manufacturing feasibility, material and methodology are the important factors that influences decision making in engineering design for marketing. Different types of theories in decision making process that helps in taking proper decision were studied in this journal. This study is based on data taken from various Research & Development centre in Industries.Â